Urinary Podocyte Loss Is Increased in Patients with Fabry Disease and Correlates with Clinical Severity of Fabry Nephropathy - Fall, Brent; Scott, C. Ronald; Mauer, Michael; Shankland, Stuart; Pippin, Jeffrey; Jefferson, Jonathan A.; Wallace, Eric; Warnock, David; Najafian, Behzad (PloS one, 2016)
Chronic kidney disease is a major complication of Fabry disease. Podocytes accumulate globotriaosylceramide inclusions more than other kidney cell types in Fabry patients. Podocyte injury occurs early in age, and is progressive. Since injured podocytes detach into the urine (podocyturia), we hypothesized that podocyturia would increase in Fabry patients and correlate with clinical severity of Fabry nephropathy. Urine specimens from 39 Fabry patients and 24 healthy subjects were evaluated for podocyturia. Most of the Fabry patients and many healthy subjects had podocyturia. The number of podocytes per gram of urine creatinine (UPodo/g Cr) was 3.6 fold greater in Fabry patients (3,741 ± 2796; p = 0.001) than healthy subjects (1,040 ± 972). Fabry patients with normoalbuminuria and normoproteinuria had over 2-fold greater UPodo/g Cr than healthy subjects (p = 0.048). UPodo/gCr was inversely related to eGFR in male patients (r = -0.69, p = 0.003). UPodo/gCr was directly related to urine protein creatinine ratio (r = 0.33; p = 0.04) in all Fabry patients. These studies confirm increased podocyturia in Fabry disease, even when proteinuria and albuminuria are absent. Podocyturia correlates with clinical severity of Fabry nephropathy, and potentially may be of prognostic value.